The policy analysis matrix applied to agricultural commodity markets - Shapiro, Barry I.; Staal, Steven J. (Lynne Rienner Publishers, Inc., 1995)
The critical role of policy in the functioning of agricultural commodity markets is being increasingly recognized. Governments often intervene in commodity markets through prices, regulations, and macro-policies. Policies affect financial returns and comparative advantage. The Policy Analysis Matrix (PAM) can be used to study policy effects at each level of the commodity chain, as well as their effects on alternative technologies. The PAM methodology identifies the cost and revenue structure of marketing activities to evaluate the effects of policy. Non-price factors, including institutional forms of market failure, are often as important as price factors in explaining market functioning. Causes of market failure and effects of investments to improve market performance can also be studied. This chapter presents the PAM methodology and illustrates its use applied to a dairy marketing system at Nyeri, Kenya.